EEG-predictor’s effectiveness of starting therapy in epilepsy de novo by adult - O. V. Grebenyuk; M. V. Svetlic; V. M. Alifirova; V. I. Jankova (Бюллетень сибирской медицины)
The study cerebral rhythm reactivity by functional load at 49 patient’s with epilepsy de novo. Make photic stimulation and cognitive activation. It was demonstrated that patients, who get remission on starting anticonvulsant therapy have intact brain reactivity.